Bone Lengthening Radius using Limb Reconstruction System - A Successful Treatment for Radius Shortening: A Case Report - Muhammad-Zaidulkhair MR; Tan RS; Kamarul IK (Malaysian Orthopaedic Journal)
Fractures of the distal radius are the most common type of forearm fractures seen in children. The most serious outcome of physeal injuries is growth arrest, which can result in deformity and even significant differences in limb length. Therefore, we'd like to share our experience with treating a patient whose left radius stopped growing after she had a physeal injury in an accident. Case presentation: we encountered a 10-year-old girl, who was involved in a road traffic accident. She sustained closed fracture distal end left radius (Salter Harris 2). She sought medical assistance late, so osteoclasis, open reduction, and a k-wire on her left radius to fix the fracture, however it was complicated with growth arrest of left radius after the bone united. It was observed that her left radius was around 4cm shorter than her right. She had an osteotomy performed on her left radius and a LRS implanted. After six months post-surgery, there was no visible shortening of her left upper limb, and the radius had grown by around 4cm. There was no neurovascular impairment after left radius lengthening. After a year had passed after her operation, the patient said she had no complaints about her left upper limb. Despite the prevalence of the ilizarov method, the monorail external fixator, also known as LRS, is an option for bone lengthening of the radius. The LRS was utilised in our situation, and the results demonstrated its usefulness.